Two new species of Paravelia Breddin, 1898 (Hemiptera: Heteroptera: Veliidae) from Colombia, with a key to Colombian Paravelia species - Padilla-Gil, Dora Nancy (Zootaxa, 2013)
Paravelia fanera sp. n. and Paravelia acantha sp. n. are described from the Andean region of Colombia. An identification key and distributional data for Colombian species are given.